An integrated mathematical model for the optimization of hybrid product-process layouts. (January 2018) - D'Antonio, Gianluca; Saja, Alex; Ascheri, Andrea; Mascolo, Julien; Chiabert, Paolo
Highlights: The flexibility provided by autonomous vehicles has to be exploited from the early design stages of a manufacturing line. A mathematical model to design hybrid product-process layouts is presented. Manufacturing cells are automatically identified and positioned to minimize the distance travelled by the products. KPIs are evaluated to assess the layout. A layout proposal can be evaluated in less than 10 seconds. Abstract: The layout of a manufacturing process plays a significant role to maintain a profitable production and make competitive a company. Product-oriented layouts aim to minimize the distance travelled by the manufactured units; the process-oriented approach attempts to maximize the saturation of the facilities. However, in many cases a hybrid approach may be necessary to achieve a compromise between the two objectives. This paper aims to present a mathematical model capable to define a hybrid product-process layout by autonomously: (i) defining the process cells and, for each of them, evaluating the number of machines necessary for stability; (ii) identifying the position of the machines within each cell; (iii) determining the best position for the cells in a given shop-floor area; (iv) evaluating a set of KPIs for the obtained layout proposal. The numerical implementation of the model led to obtain a layout proposal within 10 seconds for a process made of 30 distinct operations. The approach is validated through case-studies taken from the automotive industry; the obtained results show that the model is an effective tool to support the activities of designers of manufacturing processes.